Causative Drugs and Pattern of Severe Cutaneous Adverse Drug Reactions in Phrae Hospital - Saksit, Niwat; Suttisai, Sumitra; Piriyachananusorn, Napacha; Tiwong, Pawinee; Tassaneeyakul, Wichittra (Journal of Basic and Applied Pharmacology, 2016)
Severe cutaneous adverse drug reactions (SCARs) are severe types of adverse drug reactions which have a low incidence but a high mortality rate. This study was a survey study from databases and medical records of patients who were treated in Phrae hospital between 2007 and 2015. The objective of the study was to explore the patients’ characteristics and patterns of drugs that were implicated as the causes of SCARs including Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) or drug reactions with eosinophilia and systemic symptoms (DRESS). Results showed that during the study period, there were 47 patients who had been diagnosed as SCARs including 39 for SJS, 6 for TEN and 2 for DRESS. The mean incidence of SCARs was 5.22/million population/year. About 53% of patients were males and the mean age of SCARs patients was 53.15±17.39 years. Common causative drugs of SJS and TEN were antibiotics (25.53%), anti-convulsants (17.02%), allopurinol (14.89%) and non-steroidal anti-inflammatory drugs (8.51%). The mean exposure time of causative drugs until the first signs of SCARs occurring was 16.04 (range 1-60) days. The risk of SCARs may have been increased in patients with renal impairment. The mean hospital stay and cost for treatment of SCARs was 12.93±6.79 days and 32,112±37,414 Baht, respectively. About 46.81% of patients were suffering from complications, particularly liver impairment. The incidence of death was 4.26%.